Increasing access to specialty care for rare diseases: a case study using a foundation sponsored clinic network for patients with neurofibromatosis 1, neurofibromatosis 2, and schwannomatosis - Vanessa L. Merker; Annie Dai; Heather B. Radtke; Pamela Knight; Justin T. Jordan; Scott R. Plotkin (BMC Health Services Research, 2018)
Abstract Background Our primary aim was to assess the ability of a non-profit foundation-sponsored clinic network to facilitate access to specialized care for patients with neurofibromatoses (NF), a group of neurogenetic disorders including NF1, NF2, and schwannomatosis (SWN). Our secondary aim was to identify how our findings in NF could be applied more broadly to other rare diseases. Methods We retrospectively reviewed aggregate data on patient volume reported by specialty NF clinics in a nonprofit network from 2008 to 2015. We classified clinics as high or low volume for disease type (NF1 and NF2/schwannomatosis) and pediatric/adult care. We compared clinic-level data to self-reported patient-level data from a large online patient registry. Results Between 2008 and 2015, the number of certified NF clinics grew from 32 to 50, and annual patient volume rose from 6776 to 10,245 patients (13% of the total estimated U.S. NF patient population). For patient registry participants (n = 4476), the median driving distance to the nearest network clinic was 51.3 miles. Driving distances to reach high-volume centers were elevated for adults compared to children (295.8 vs. 67.9 miles), and schwannomatosis and NF2 patients compared to NF1 patients (310.9 vs. 368.1 vs. 161.7 miles). Of registry participants reporting their location of care (n = 2271), only 43.2% received care in a network specialty clinic, with especially low rates of attendance in the Southwest and Far West. Conclusions While the number of certified NF clinics and volume of patients seen in these clinics has increased, many NF patients still do not attend specialty clinics and/or travel a significant distance for care. Geographic access to care is more limited for adults, patients with rarer conditions, and patients in the Western U.S. Potential measures to improve access to specialty care for people living with NF and other rare diseases are discussed.